Circulating cardiac MicroRNAs safeguard against dilated cardiomyopathy - Xiaolei Cheng; Dongdong Jian; Junyue Xing; Cihang Liu; Yong Liu; Cunying Cui; Zhen Li; Shixing Wang; Ran Li; Xiaohan Ma; Yingying Wang; Xiaoping Gu; et al. (Clinical and Translational Medicine, 2023)
Abstract Background Cardiac‐resident or ‐enriched microRNAs (miRNAs) could be released into the bloodstream becoming circulating cardiac miRNAs, which are increasingly recognized as non‐invasive and accessible biomarkers of multiple heart diseases. However, dilated cardiomyopathy (DCM)‐associated circulating miRNAs (DACMs) and their roles in DCM pathogenesis remain largely unexplored. Methods Two human cohorts, consisting of healthy individuals and DCM patients, were enrolled for serum miRNA sequencing (10 vs. 10) and quantitative polymerase chain reaction validation (46 vs. 54), respectively. Rigorous screening strategy was enacted to define DACMs and their potentials for diagnosis. DCM mouse model, different sources of cardiomyocytes, adeno‐associated virus 9 (AAV9), gene knockout, RNAscope miRNA in situ hybridization, mRFP‐GFP‐LC3B reporter, echocardiography and transmission electron microscopy were adopted for mechanistic explorations. Results Serum miRNA sequencing revealed a unique expression pattern for DCM circulating miRNAs. DACMs miR‐26a‐5p, miR‐30c‐5p, miR‐126‐5p and miR‐126‐3p were found to be depleted in DCM circulation as well as heart tissues. Their expressions in circulation and heart tissues were proven to be correlated significantly, and a combination of these miRNAs was suggested potential values for DCM diagnosis. FOXO3, a predicted common target, was experimentally demonstrated to be co‐repressed within cardiomyocytes by these DACMs except miR‐26a‐5p. Delivery of a combination of miR‐30c‐5p, miR‐126‐5p and miR‐126‐3p into the murine myocardium via AAV9 carrying an expression cassette driven by cTnT promoter, or cardiac‐specific knockout of FOXO3 (Myh6‐CreERT2, FOXO3 flox+/+) dramatically attenuated cardiac apoptosis and autophagy involved in DCM progression. Moreover, competitively disrupting the interplay between DACMs and FOXO3 mRNA by specifically introducing their interacting regions into murine myocardium crippled the cardioprotection of DACMs against DCM. Conclusions Circulating cardiac miRNA‐FOXO3 axis plays a pivotal role in safeguarding against myocardial apoptosis and excessive autophagy in DCM development, which may provide serological cues for DCM non‐invasive diagnosis and shed light on DCM pathogenesis and therapeutic targets.